1996
DOI: 10.1159/000262156
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Incidence Rates and Intraoral Distribution of Root Caries among Community-Dwelling Older Adults

Abstract: The 5-year incidence and intraoral distribution of decayed and filled root surfaces were evaluated in 379 black and 323 white residents of North Carolina aged 65 and older. During the period of study, approximately 39% of blacks developed at least one root DFS compared with 52% for whites (Wald χ2 test, p = 0.062). When the results were calculated using the net root DFS increment, blacks did not have significantly higher rates than whites over the 5-year study period (0.52 surfaces/person versus 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…This 94% prevalence figure (only the 24-month time point was included, with no assessment of incident change between baseline and 24 months) compares to a 96% prevalence figure at the baseline examination . Our 6% prevalence for recurrent caries is within the range of 2-12% reported by previous studies [Hand et al, 1988a, b;Joshi et al, 1993;Lawrence et al, 1996].…”
Section: Comparisons Of Incidence To Other Studiessupporting
confidence: 87%
“…This 94% prevalence figure (only the 24-month time point was included, with no assessment of incident change between baseline and 24 months) compares to a 96% prevalence figure at the baseline examination . Our 6% prevalence for recurrent caries is within the range of 2-12% reported by previous studies [Hand et al, 1988a, b;Joshi et al, 1993;Lawrence et al, 1996].…”
Section: Comparisons Of Incidence To Other Studiessupporting
confidence: 87%
“…From those reports, dental longitudinal studies of older people in Iowa, North Carolina, Ontario and South Australia were identified which met the entry criteria for this study (extending the searches substituting, in turn, 'follow-up studies', 'longitudinal studies' and 'prospective studies' for the term 'cohort studies' resulted in no further studies being found which met those criteria). There were seven reports identified from those included in the current study, of which two described coronal caries, 7,8 three described root surface caries, [9][10][11] and two presented data on both types of caries. 12,13 All but two of the reports described changes over 3 years; the remaining two covered a 5-year period.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 All but two of the reports described changes over 3 years; the remaining two covered a 5-year period. 9,13 A summary of the baseline estimates for caries prevalence and severity from earlier reports in the Iowa, 14 North Carolina, 15 Ontario 16 and South Australian 17 studies is presented in Table 1. Overall, the dental characteristics at baseline were quite similar, with the notable exception of the North Carolina blacks, who had (on average) fewer teeth present and lower caries experience.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a longitudinal study of the elderly in North Carolina, Blacks were more likely to develop decay in the roots of teeth than Whites (68). In a longitudinal study of Florida adults 45 years and older with at least one tooth, 45% had active decay of the crowns of the teeth, and 10% had one or more infected fragments of broken teeth in the jawbone.…”
Section: Dental Caries Among Adultsmentioning
confidence: 99%